Parámetros linguo-pragmáticos de los mini textos literarios en inglés y ucraniano - Orenchak, Olha; Novikova, Olga; Yeshchenko, Tetyana; Truba, Hanna; Bilokonenko, Liudmyla (My University, 2022)
The problem of analysing the impact of literary mini-texts on a wide range of audiences has been partially covered so far. The aim of the article was to investigate the analysis of hidden frame structures from the respondents’ answers on the basis of literary mini-texts about fashion. The functional-pragmatic aspect of the actualized texts prepared for the respondents, which was selected for analysis, allows identifying the hidden purpose and meaning of literary mini-texts in the fashion discourse in general. The study involved discursive, intentional methods, the method of cognitive modelling, a combination of assignments such as “multiple choice” and free associative experiment (the method of enumeration). The experiment identified a model of a communicative event, the language structure of which is the most common in Vogue magazine’s literary mini-texts. The study showed the ratio of all types of communicative events in mini-texts, where the concepts of “challenge”, “time”, “effortlessness” are verbalized, each having certain language formulas in literary mini-texts about fashion. The materials of empirical research can be useful for methodological recommendations for university students when deepening multi-vector works on philology. A promising area of research is the selection and description of key concepts of the discourse of mini-texts in diachrony.
Novikova Olga Parámetros linguo-pragmáticos de los mini textos literarios en inglés y ucraniano / Olga Novikova, Tetyana Yeshchenko, Olha Orenchak, Hanna Truba, Liudmyla Bilokonenko // Apuntes Universitarios. – 2022. - Vol. 12, Núm. 4. – P. 40-61.
Keywords: pragmatics of the text; frame structure; mini-text; free associative experiment; concept